Evaluating the Effectiveness of Poster & Picture Card Media in Teaching the Water Cycle to Elementary Students - Nikmah Fitria Surya; Wenda, Dhian Dwi Nur (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2023)
This study explores the validity, practicality, and effectiveness of Postcard learning media in the classroom. Employing a Research and Development approach, the study utilized the ADDIE model, encompassing Analysis, Design, Development, Implementation, and Evaluation stages. The research was conducted with 17 fifth-grade students at SDN 1 Watudandang. The study involved quantitative analysis to assess the Postcard learning method's implementation, employing a variety of data collection techniques. These included validity questionnaires from media and material experts, teacher and student response questionnaires, and pretest-posttest scores. Validity testing revealed that the Postcard learning media were rated as